2006
DOI: 10.1016/s0022-5347(06)00569-6
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Methods of Diagnosing Bladder Outlet Obstruction in Men. Part 1: Nonurodynamic Approach

Abstract: Ultrasound derived measures such as bladder wall thickness and bladder weight offer a promising possibility of diagnosing bladder outlet obstruction noninvasively. However, further reproducibility and large accuracy studies with better methodological standards are required before they can replace pressure flow studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 47 publications
1
33
1
3
Order By: Relevance
“…A number of studies reviewing the evidence for various noninvasive urodynamic tests have been published in recent years [49][50][51][52][53][54][55][56]. All reviews have reported similar findings to the present review: some noninvasive tests appear promising, especially in combination, but further investigation is required before they can replace invasive urodynamics.…”
Section: How the Review Compares To Previous Reviews/guidelinessupporting
confidence: 73%
“…A number of studies reviewing the evidence for various noninvasive urodynamic tests have been published in recent years [49][50][51][52][53][54][55][56]. All reviews have reported similar findings to the present review: some noninvasive tests appear promising, especially in combination, but further investigation is required before they can replace invasive urodynamics.…”
Section: How the Review Compares To Previous Reviews/guidelinessupporting
confidence: 73%
“…Though it may be a condition related to bladder outlet obstruction, hypocontractile bladder may also be responsible. [6] Therefore, increased PVR is insufficient to define the type or degree of disease. However, interpretation of significant PVR in favor of isolated benign prostatic obstruction (BPO) has been proposed in numerous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] Similarly, recurrent urinary tract infection has been reported to be caused by residual urine in the elderly population and in girls. [6,16,17] Klarskov et al demonstrated that PVR increased the risk of acute urinary retention 3.6 times. [18] Increased PVR or low Qmax value may suggest bladder outlet obstruction and/or underactive bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, augmentation procedures should be optimized to be specifically targeted to regions with the most morphological alterations. Current in vivo imaging methods such as x-ray, ultrasound and MRI can only identify anatomical changes in the bladder that are spatially nearly uniform throughout the bladder wall [5,14]. Therefore, new in vivo imaging techniques are needed that can identify the regions with the most pronounced morphological changes, to localize and optimize augmentation procedures.…”
Section: Introductionmentioning
confidence: 99%